Dysregulation of immune cell and cytokine signalling correlates with clinical outcomes in myelodysplastic syndrome (MDS). (3rd February 2022) - Chee, Lynette; Ritchie, David; Ludford‐Menting, Mandy; Ripley, Jane; Chung, Jessica; Park, Daniel; Norton, Sam; Kenealy, Melita; Koldej, Rachel
Abstract: Objectives: Myelodysplastic syndromes (MDS) are characterised by ineffective haematopoiesis. Although hypomethylating agents (HMA) have improved survival in higher‐risk MDS, most patients eventually succumb to progressive disease. Utilising samples collected prospectively from three MDS clinical trials, we analysed genetic and immunological biomarkers and correlated them with clinical outcomes. Methods: A hundred and fifty four samples were analysed from 133 de novo MDS patients for T‐cell and myeloid cell immunophenotyping and gene expression analysis. Treatments were with HMA or immunomodulatory drug (IMiD) alone or in combination. Results: We observed differences in immune cell subsets between lower‐ and higher‐risk IPSS groups with NKT cells, MDSCs, intermediate‐proinflammatory and non‐classical monocytes being higher in the latter group, while naïve CD4+ T cells were reduced. Intermediate‐proinflammatory monocytes were increased in non‐responders and those failing to achieve at least a haematological improvement. Proinflammatory NKT cells were increased at diagnosis for patients failing to derive clinical benefit after 12 months of treatment. Gene expression analysis of paired bone marrow (BM) colony‐forming units (CFUs) from diagnosis and 4 cycles post‐treatment confirmed that genes involved in cytokine signalling were downregulated in C4 normal colonies. Conclusions: These findings support the central roles of dysregulation in innate immunity and inflammatory signalling in the pathogenesis of MDS which correlated with clinical outcomes post‐treatment.